Moving beyond data integration with data collaboration - DeMers, Dan; Jaswal, Karanjot (O'Reilly Media, Inc., 2023)
How can you maximize data collaboration across your organization without having to build integrations between individual applications, systems, and other data sources? Data collaboration architectures that don't depend on integrations aren't a new idea, but they've assumed greater urgency as organizations increasingly struggle to manage the ever-growing numbers of data sources that exist inside their IT estates. In this report, Cinchy cofounders Dan DeMers and Karanjot Jaswal show CIOs, CTOs, CDOs, and other IT leaders how to rethink their organization's approach to data architectures, data management, and data governance. You'll learn about different approaches to creating data platforms that liberate and autonomize data, enable agile data management, apply consistent data access controls, and maximize visibility without requiring application-specific integrations. With this report, you'll discover: Why data integration is often handled piecemeal--combining one app with another rather than integrating all apps together How data collaboration platforms enable data sharing across all apps, systems, and sources without application-specific integrations Four major platforms you can use to make data available to all applications and services: Cinchy, K2View, Microsoft Dataverse, and The Modern Data Company Principles and practices for deploying the data collaboration platform of your choice Dan DeMers is the CEO and cofounder of Cinchy. Karanjot Jaswal is cofounder and CTO of Cinchy.